The Effect of Tai Chi Gymnastic on Decreasing Low Back Pain of Elderly Farmers - Endang Yuswatiningsih; Dyah Elvi Meiedietik; Nining Mustika Ningrum (Aloha International Journal of Health Advancement (AIJHA), 2019)
Low back pain is one of health problems that distrub a daily comfort and activities. Low back pain increasing along with the increase of age and bent forward position which was applied in daily working by elderly farmers. The aim of this study was to analyze the effect of tai chi gymnastic on decreasing low back pain of elderly farmers. The research design of this study was one group of pre test-post test design. The population objects in this study were all of elderly farmers with low back pain complaints which were recorder in the elderly medical center, which contained of 32 samples in total and were determined using simple random sampling technique. The independent variable in this study was Tai Chi gymnastic and low back pain of elderly farmers as dependent variable. Verbal descriptor scale was used as the data collection method. This study was using editing, coding, scoring and tabulating as data processing techniques, and Wilcoxon signed rank test on testing the statistics. The result of this study showed the percentages of each low back pain phases, which contained of 41% mild low back pain, 50% moderate low back pain and 9% hard low back pain before tai chi gymnastics. Besides, the percentages of low back pain phases after tai chi gymnastic were 69% for mild low back pain, 31% moderate low back pain and 0% hard low back pain. The result of Wilcoxon signed rank test showed that the p-value = 0.001 < 0.05, so that H0 was rejected. The conclusion there was an effect of Tai chi gymnastic on decreasing low back pain of elderly farmers. Keywords: low back pain; elderly farmers; Tai chi gymnastic